2016
DOI: 10.1149/2.0051612jss
|View full text |Cite
|
Sign up to set email alerts
|

Deep Electron Traps Responsible for Higher Quantum Efficiency in Improved GaN/InGaN Light Emitting Diodes Embedded with SiO2Nanoparticles

Abstract: Deep traps spectra are compared for GaN/InGaN light emitting diodes with and without a template embedded with SiO2 nanoparticles underlying the active multiple quantum well region. The structures with SiO2 nanoparticles show a higher internal quantum efficiency which correlates with a lower concentration of deep traps with level near Ec-0.6 eV as compared to reference structures. We discuss complications in deep traps analysis coming from the freeze-out of Mg acceptors and the choice of proper biasing conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The density of extended defects in these structures was typical of good quality blue LEDs. 28 The structural properties were unaffected by electron irradiation up to the highest fluence used.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The density of extended defects in these structures was typical of good quality blue LEDs. 28 The structural properties were unaffected by electron irradiation up to the highest fluence used.…”
Section: Resultsmentioning
confidence: 95%
“…27 These were performed at a probing signal frequency of 10-50 kHz to account for strong capacitance reduction at low temperatures caused by the freeze-out of holes at Mg acceptors in the p-GaN contact layer. 24,28,29 EL measurements were performed at 300 K as a function of drive current to assess effects of leakage current, the presence of SRH traps giving rise to non-radiative recombination at low currents, and the EL efficiency droop at high drive currents.…”
Section: Methodsmentioning
confidence: 99%
“…The spectrum showed a clear optical threshold near a photon energy of 1.3 eV and a near plateau between 1.5 and 2 eV. The concentration of the center responsible for this photocapacitance was calculated as the difference between the C – V concentration at 2 eV and in the dark and it was ∼10 16 cm −3 . From the concentration profile under illumination, the centers are located in the GaN barrier of the QW.…”
Section: Resultsmentioning
confidence: 99%
“…Figure (b) shows an ODLTS spectrum taken before irradiation with excitation from 3.4 eV LEDs. The spectra are for temperatures higher than 200 K – at lower temperatures the capacitance decreased strongly due to freeze‐out of Mg acceptors in p‐GaN and reliable DLTS measurements were not practicable . The quiescent bias used for DLTS and ODLTS measurements in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In composition fluctuation also affected the efficiency [24]. In addition, it has been observed that the density of deep Shockley-Hall-Read traps in modified structures was measurably lower than in reference structures [25]. Experiments with electron irradiation indicate that the increase in concentration of some of the detected deep traps correlated with the decrease of the EQE of irradiated LEDs [26].…”
Section: Resultsmentioning
confidence: 99%